TINJAUAN MOTIVASI INTRINSIK ATLET BOLA BASKET DALAM MENGIKUTI LATIHAN PADA CLUB BASKET FIRST BASO - Al Faradisi, Muhammad Rayhani; Putra, Yogi Arnaldo; Sin, Tjung Haw; Yenes, Ronni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low attendance consistency and limited training facilities are key psychological challenges for sub-district athletes. This study evaluates intrinsic motivation of First Baso Basketball Club athletes based on stimulation, desire to learn, and personal accomplishment. A quantitative descriptive design was used with 20 players selected through total sampling. Data were collected using a 15-item Likert questionnaire and analyzed descriptively. Results show high intrinsic motivation with an average score of 78.25%. Stimulation scored highest at 81.50%, followed by desire to learn at 79.25%, and personal accomplishment at 74.00%. Overall, athletes remain committed despite limited facilities. Strengthening personal goal setting is recommended to sustain training participation during non-competition periods.